Electric field change measurements of a terrestrial gamma ray flash. Issue 10 (27th May 2017) - Marshall, Thomas; Karunarathne, Sumedhe; Stolzenburg, Maribeth; Briggs, Michael; Cramer, Eric S.; Mailyan, Bagrat G.; McBreen, Shelia; Roberts, Oliver J.; Stanbro, Matthew
Abstract: The electric field change (E‐change) data presented herein provide a complementary view of a known terrestrial gamma ray flash (TGF), namely, TGF1 from Cummer et al . (2014 ). The main E‐change pulse coincident with TGF1 was likely an initial breakdown (IB) pulse of an intracloud (IC) flash since it had the typical characteristics of such an IC IB pulse: a bipolar shape with a positive leading peak and a duration of 47 μs. The IB pulse was especially energetic, with an estimated zero‐to‐peak amplitude between 36 and 47 V/m range normalized to 100 km (compared to an average IC IB pulse amplitude of 1.5 V/m). The positive peak of the IB pulse occurred 19 μs after the beginning of the pulse. The first and most energetic gamma ray (7.6 MeV) detected in TGF1 occurred at 9 ± 10 μs after the beginning of the IB pulse. Thus, at the earliest the first detected gamma ray may have been produced just before or at the beginning of the IB pulse; at the latest, it may have been produced at the peak of the IB pulse. Key Points: The electric field pulse associated with a TGF is identified as an initial breakdown (IB) pulse of an intracloud flash with 47 microseconds duration The IB pulse had an exceptionally large zero‐to‐peak amplitude that was a factor of 25–30 larger than typical of IB pulses The first TGF gamma ray detected was the most energetic (7.6 MeV) and occurred at 9 ± 10 microseconds after the beginning of the IB pulse